Reasoning Talk at Chinese Families’ Dinner Table: Across Three Generations and Different Communicative Contexts - Liu, Lifang; Zheng, Feiyi; Sheng, Ling; Hao, Yijun; Hu, Jiangbo (Frontiers in Psychology, 2021)
TThis study examines the feature of reasoning talk used by 357 Chinese families at the dinner table across three generations under the background of co-parenting and in consideration of different communicative contexts. Drawing upon Hasan’s semantic framework, reasons were mainly coded as logical or social types. The communicative context of reasoning talk was categorized into contextualized (meal-related) and decontextualized topics. The families’ reasoning talk account for only 7.863.85% of the total language, when the proportion of social reasoning was found slightly higher than that of logical reasoning. Specifically, mother’s total reasoning talk was counted significantly above other family members, while there were no significant differences among the other participants. The effect of the communicative contexts on family members’ social reasoning were found. The reasoning talk grounded on local rules and coercive power occurred significantly more frequently in contextualized than decontextualized context. Higher rate of local reasoning talk of all family members appeared in contextualized than decontextualized context, and this gap was particularly obvious among mothers. These findings reveal the significant role of mothers in family communications and confirm the pedagogical values of decontextualized communicative context for promoting children’s learning opportunities at the dinner table.